Low rates of bedrock outcrop erosion in the Central Appalachian mountains inferred from in situ 10Be - Portenga,EW; Bierman,PR; Rizzo,DM; Rood,DH (Bulletin of the Geological Society of America, 2013)
Bedrock outcrops are common on central Appalachian Mountain ridgelines. Because these ridgelines define watersheds, the rate at which they erode infl uences the pace of landscape evolution. To estimate ridgeline erosion rates, we sampled 72 quartz-bearing outcrops from the Potomac and Susquehanna River Basins and measured in situ-produced 10Be. Ridgeline erosion rates average 9 ± 1 m m.y.-1 (median = 6 m m.y.-1), similar to 10Be-derived rates previously reported for theregion. The range of erosion rates we calculated refl ects the wide distribution of samples we collected and the likely inclusion of outcrops affected by episodic loss of thick slabs and periglacial activity. Outcrops on main ridgelines erode slower than those on mountainside spur ridges because ridgelines are less likely to be covered by soil, which reducesthe production rate of 10Be and increases the erosion rate of rock. Ridgeline outcrops erode slower than drainage basinsin the Susquehanna and Potomac River watersheds, suggesting a landscape in disequilibrium. Erosion rates are more similar for outcrops meters to tens of meters apart than those at greater distances, yet semivariogram analysis suggests that outcrop erosion rates in the same physiographic province are similar even though they are hundreds of kilometers apart. This similarity may refl ect underlying lithological and/or structural properties common to each physiographic province. Average 10Be-derived outcrop erosion rates are similar to denudation rates determined by other means (sediment fl ux, fission-track thermochronology, [U-Th]/He dating), indicating that the pace of landscape evolution in the central Appalachian Mountains is slow, and has been since post-Triassic rifting events. © 2013 Geological Society of America.